Improving phosphorus removal in aerobic granular sludge processes through selective microbial management. (July 2016) - Henriet, Olivier; Meunier, Christophe; Henry, Paul; Mahillon, Jacques
Highlights: Bacterial diversity was assessed in granules separated by isopycnic centrifugation. Dense aerobic granules contain a higher proportion of Candidatus Accumulibacter. Excessive shortening of the settling time was detrimental to P removal. A higher settling time with homogeneous settled sludge removal improved P removal. The biomass management improved and stabilized P removal over 90%. Abstract: This study aimed to improve phosphorus removal in aerobic granular sludge sequential batch reactors (AGS-SBR) by a differential selection of the granules containing the highest proportion of phosphate accumulating organisms (PAOs). The abundance of PAOs in granules with different density was analyzed by PCR-DGGE, pyrosequencing and qPCR. Dense granules contained a higher proportion of Candidatus Accumulibacter (PAO) with a 16S rRNA gene frequency up to 45%. Starting with an AGS-SBR with low height/diameter ratio performing unstable P removal, two strategies of biomass removal were assessed. First, a high selective pressure (short settling time) was applied and second, an increase of the settling time was combined with a homogeneous purge of the sludge bed. The first strategy resulted in a reduction of P removal efficiency while the second improved and stabilized P removal over 90%. This study offers a new approach of biomass management in AGS-SBR.